PERAN KOMUNITAS RACIKA PALM DALAM PENGELOLAAN SUMBER DAYA AIR BERKELANJUTAN DI KABUPATEN BATANG - Nugraha, Mustofa Fajar; Ajeng Mega Indriyani, Retno; Januar Hidayat, Reza (RISTEK : Jurnal Riset, Inovasi dan Teknologi Kabupaten Batang, 2025)
Human activities are causing global environmental changes that affect climate and water quality. Although water is crucial for life and the economy, previous management practices have not been sustainable. With increasing water demand and limited availability, new approaches to water resource management are needed for a sustainable future. Water resource management practices in Indonesia face challenges from social subsystems related to community participation in water resource management. This study employs a qualitative descriptive method supported by a Narrative Literature Review (NLR). Community participation in the Integrated Water Resources Management (IWRM) process has been emphasized by national regulations and researchers. The "Bottom-Up Planning & Management" approach involves active participation from groups or communities directly involved in resource management, as well as stakeholders affected by decisions made. The local initiative of the Racika Palm community in water resource management has led to social innovations through watershed conservation programs via reforestation, community empowerment, education on water utilization, and policy advocacy through TKPSDA and other forums. Challenges in developing community participation include financial limitations and insufficient technological utilization to expand the impact of community roles. Communities need to leverage social media and technological innovations, such as Smart Water Management (SWM), to enhance the effectiveness of water resource conservation programs. Through community involvement with broader impacts, the vision of integrated water resource management can be achieved.